WINTER HARDINESS OF BREAD WHEAT FROM THE VIR COLLECTION IN ENVIRONMENTS OF THE NORTHWESTERN AND CENTRAL BLACK SOIL REGIONS OF RUSSIA - N. S. Lysenko; V. F. Loseva; O. P. Mitrofanova (Труды по прикладной ботанике, генетике и селекции)
Background. Winter wheat resistance to adverse wintering conditions is one of the most important adaptive characteristics. To obtain high yields, modern wheat cultivars should have various protective reactions. For their successful combination in one genotype, the availability of appropriate initial material is of great importance. In Russia, the accessions from the VIR collection are traditionally used as initial material for wheat breeding. The aims of the present study were (1) to evaluate winter hardiness in accessions from the VIR collection in a field test, and (2) to use the obtained data and those on the geographical origin of accessions for making up the target sub-collection and performing its eco-geographical studies.Materials and methods. The initial sample for field screening contained 431 accessions of common winter wheat from different regions of Russia and the former USSR, and 484 accessions from 18 foreign countries. Winter hardiness of these accessions was tested in the environmental conditions of the Northwestern region (Pushkin, 59°41′N 30°20′E, 2006/2007, 2007/2008 and 2013/2014) and of the Central Black Soil region (Yekaterinino, 52°59′N 40°50′E, Tambov Province, 2007/2008 and 2008/2009). The degree of winter hardiness was determined in accordance with the technique developed at VIR.Results and conclusions. In 2006/2007, in Pushkin, a high and a very high degree of winter hardiness was displayed by 114 accessions with the origin from Russia and the former USSR as well as by 12 accessions from foreign countries. Based on the obtained data and taking into account the diversity of the geographical origin of accessions, the target sub-collection was formed, whose accessions were subjected to eco-geographical two-year field studies (Pushkin, 59°41′N 30°20′E, 2007/2008, 2013/2014, and Yekaterinino, 52°59′N 40°50′N, Tambov Province, 2007/2008, 2008/2009). The Friedman’s variance analysis has shown that variation on winter hardiness in 158 accessions from the target sub-collection was determined by the environmental conditions of wheat cultivation (χ2э = 256.7; df = 4; χ2W=0.05 = 9.5) and by genetic differences between accessions (χ2э = 239.3; df = 157; χ2W=0.05 = 187.2) at that effect of the prior was stronger than that of the latter. By using the cluster analysis (k-means algorithm), the target sub-collection structure has been revealed. Twelve accessions that overwintered well at both geographical locations during all the years of testing were identified.